Epidemiology of herpes simplex virus type 1 in Canada: systematic review, meta-analyses, and meta-regressions - Sawsan AlMukdad; Sawsan AlMukdad; Manale Harfouche; Manale Harfouche; Uzma S. Farooqui; Lana Aldos; Laith J. Abu-Raddad; Laith J. Abu-Raddad; Laith J. Abu-Raddad; Laith J. Abu-Raddad (Frontiers Media S.A., 2023)
BackgroundThe objective of this study was to characterize herpes simplex virus type 1 (HSV-1) epidemiology in Canada.MethodsHSV-1 publications as recent as December 6, 2021 were systematically reviewed, synthesized, and reported following PRISMA guidelines. Meta-analyses and meta-regressions were conducted.ResultsHSV-1 measures were extracted from 22 studies and included 32 overall seroprevalence measures (79 stratified), 2 overall proportions of HSV-1 detection in clinically diagnosed genital ulcer disease (2 stratified), and 8 overall proportions of HSV-1 detection in laboratory-confirmed genital herpes (27 stratified). Pooled mean seroprevalence was 19.1% [95% confidence interval (CI): 12.6-26.4%] among healthy children and 51.4% (95% CI: 47.3-55.5%) among healthy adults. Pooled mean seroprevalence among healthy general populations increased with age, with the lowest being 35.7% (95% CI: 29.1-42.6%) among individuals <20 years of age, and the highest being 70.0% (95% CI: 54.8-83.2) among individuals ≥40 years. Seroprevalence increased by 1.02-fold (95% CI: 1.01-1.04) per year. Pooled mean proportion of HSV-1 detection in genital ulcer disease was 30.8% (95% CI: 12.6-52.8%). Pooled mean proportion of HSV-1 detection in genital herpes was 37.4% (95% CI: 29.5-45.6%) and was highest in women and in young persons. Proportion of HSV-1 detection in genital herpes increased by 1.04-fold (95% CI: 1.00-1.08) per year.ConclusionsHSV-1 epidemiology in Canada appears to be shifting toward less oral acquisition in childhood and more genital acquisition in adulthood, particularly among youth. Both HSV-1 seroprevalence and proportion of HSV-1 detection in genital herpes are increasing with time.